Coronary sinus reducer device for the treatment of refractory angina therapy. A multicentric initial experience. (3rd October 2022) - Dias Ferreira Reis, J P; Brizido, C; Madeira, S; Ramos, R; Almeida, M; Cacela, D
Abstract: Introduction: The coronary sinus Reducer device (CSRD) emerged as a complementary therapy in patients with severe angina refractory to optimal medical therapy and not amenable to revascularization. Our aim was to assess the safety and efficacy of the CSRD in a real-world setting. Methods: Twenty-six patients with refractory angina (RA), evidence of myocardial ischemia attributable to the left coronary artery unsuitable for revascularization were treated with the CSRD at two centres between May 2017 and July 2019. Safety endpoints were procedural success and complications. Efficacy endpoints, assessed at 6-month follow-up, were a reduction in CCS class, improvement in quality of life (QoL) assessed using the short version of the Seattle Angina Questionnaire (SAQ-7) and reduction in anti-anginal therapy. Results: Twenty-three patients had end-stage CAD without revascularization targets and 3 patients had microvascular disease without epicardial stenosis. Procedural success was achieved 23 patients, with 2 device/procedural-related complications and one anatomically-related failure to deliver the device. Ultimately 25 patients implanted the device and entered the efficacy analysis. Eighteen patients (75.0%) had at least 1 reduction in CCS class, 41.7% had at least 2 class reductions, and 16.7% became asymptomatic, with a mean reduction of CCS class of 1.3±0.2 (p=0.001) at 6-month follow-up. All SAQ-7 domains improved, namely physical limitation (p=0.001), angina frequency (p=0.005) and QoL (p=0.006). There was a mean reduction of anti-ischemic drugs from 3.4±1.1 to 2.9±1.2 (p=0.010). Conclusion: In this real-world, multicentric experience, implantation of the CSRD was associated with improvement of angina and QoL in patients with RA. Funding Acknowledgement: Type of funding sources: None.